(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, based on the one-signed Green’s function and the compact results on the infinite interval, we obtain the existence and multiplicity of positive solutions for the boundary value problems cases Δ^2 x(n-1)-p(n)Δ x(n-1)-q(n)x(n-1)+f(n,x(n))=0, &nN, α x(0)-β Δ x(0)=0, & _n→∞x(n)=0 casesby the fixed point theorem in cones. The main results extend some results in the previous literature.